Formulation and evaluation of gel vehicles for oral administration of pellets with diclofenac - Stojmenovski, Aneta; Mirjanić, Maja; Gatarić, Biljana; Bubić Pajić, Nataša; Račić, Andjelka (Archives of Pharmacy, 2022)
To address the administration difficulties associated with use of solid or non-viscous oral dosage forms, oral gels have been proposed as a promising formulation approach. The aim of this study was formulation and evaluation of gels for oral administration of diclofenac pellets, using carbomer (0.5 % w/w) (G1), sodium alginate (5% w/w) (G2), and gelatin (2.5% w/w) (G3) as viscosity increasing agents. Pellets containing 75 mg diclofenac (25 mg in gastro-resistant pellets and 50 mg in prolonged-release pellets) were extracted from commercially available capsules and dispersed in 10 g of the gel vehicle. Physicochemical properties (appearance, clarity, pH, viscosity) of the prepared formulations were tested. Dissolution tests were performed using basket apparatus (100 rpm), in two phases (acidic and basic, using 0.1 M HCl and phosphate buffer (pH 7.5), respectively), during 24 h. The clarity, pH and viscosity of all formulations were in an acceptable range for oral gels. Different dissolution patterns were observed for the reference product and tested formulations, except formulation G3. The preserved high viscosity of a carbomer gel in a phosphate buffer, inhibited the dissolution of diclofenac. The amount of the drug dissolved at the end of the experiment was increased compared to the commercial capsules (80.1%) and was 92.0% (G2) and 100.8% (G3), respectively. Diclofenac-loaded pellets were successfully incorporated in oral gels. The gels of sodium alginate and gelatin have potential to facilitate swallowing and can be considered as an appealing formulation strategy for overcoming the administration problems of other oral dosage forms.